2024
DOI: 10.1038/s41598-024-54716-3
|View full text |Cite
|
Sign up to set email alerts
|

Global prevalence of functional dyspepsia according to Rome criteria, 1990–2020: a systematic review and meta-analysis

Kwanjoo Lee,
Chang-il Kwon,
Abdullah Özgür Yeniova
et al.

Abstract: Although functional dyspepsia (FD) is a common functional gastroduodenal disorder with a high socioeconomic burden, little is known about its global prevalence. Thus, we performed a comprehensive study to estimate long-term trends in the prevalence of FD. We searched PubMed/MEDLINE, Embase, and Google Scholar from 1990 to 2022 for population-based studies that reported the prevalence of FD in adults (≥ 18 years old) according to Rome I, II, III, or IV criteria. The prevalence of FD was extracted from included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Although the pooled prevalence of FD gradually decreased due to increasing medical level and improved life quality from 1990 to 2020 (12.4% [8.2–18.3] in 1990–2002 versus 7.3% [6.1–8.7] in 2013–2020) [ 3 ], FD-related health care operations are still imposing a significant financial burden on the healthcare system, whose global annual cost exceeds $18 billion [ 24 , 25 ]. After considering for something like the price of medical care, drug rehab, and time off work, the average annual cost per FD patient in the US is $699 [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the pooled prevalence of FD gradually decreased due to increasing medical level and improved life quality from 1990 to 2020 (12.4% [8.2–18.3] in 1990–2002 versus 7.3% [6.1–8.7] in 2013–2020) [ 3 ], FD-related health care operations are still imposing a significant financial burden on the healthcare system, whose global annual cost exceeds $18 billion [ 24 , 25 ]. After considering for something like the price of medical care, drug rehab, and time off work, the average annual cost per FD patient in the US is $699 [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common functional gastrointestinal disorders is functional dyspepsia (FD) [ 1 , 2 ]. According to ROME criteria, population-based studies reported that the overall global pooled prevalence of FD in adults from 1990 to 2022 was 8.4%, which was even higher in developing countries (9.0%) [ 3 ]. Low cure rates, frequent flare-ups, and persistent symptoms are all characteristics of FD that impair patients’ quality of life and cause a greater financial healthcare burden which reaches $1.84 billion per year in the USA [ 4 – 6 ].…”
Section: Introductionmentioning
confidence: 99%